Pré-mediação e transformação do conflito: uma relação à luz do acesso à justiça - Porto, Júlia Pinto Ferreira (2018)
This thesis deals with the possibility of conflict transformation, emphasizing the pre-mediation stage of the mediation. The main objective is to construct a theoretical framework aimed at this premediation, under the justification of being an incipient subject, and because mediation is a practice widely recommended and currently disseminated in justice policies. The hypothesis is that if mediation is a mechanism for expanding access to justice, the moment of pre-mediation has particularities that influence this process, especially regarding the possibility of the conflict being transformed. For this, the dialectical process is used for the construction of this idea, and it starts from access to justice as a theoretical object constituted by the result of the Florence Project, which became a reference for the formulation of studies and policies of a legal field through the stipulation of what he calls the "approach to access to justice". The Bourdieusian notions of "juridical field" and "habitus" were allied to this. Next, "transformative mediation" is analyzed as a platform for symbolic transformation of conflicts and social change through the habitus. Pre-mediation, in this scenario, makes it possible to uncover the mediator's relationships in relation to the formal practices of the law; of mediandos, in relation to their conflicts, from a performance of the mediator. It is maintained that in pre-mediation there is a proposal to loosen a certain formalism common to the practices of the legal field, but that some ritual is still ongoing, and that the transformation of conflicts occurs through a change in the basis of relationships and worldviews of mediandos. Finally, it is concluded that the transformation of conflicts is possible, but deals with the limitation of internal availability of mediandos, and that the democratization of access in pre-mediation does not necessarily operate as an extension to popular social strata